2004
DOI: 10.1577/t02-168
|View full text |Cite
|
Sign up to set email alerts
|

Mechanistic Linkage of Hydrologic Regime to Summer Growth of Age-0 Atlantic Salmon

Abstract: Significant reductions in juvenile stream salmonid growth have been observed in association with low summer flow, but underlying mechanisms are poorly understood and predictive power is limited. We conducted a stage-specific analysis of the relationship between summer flow and the growth of age-0 Atlantic salmon Salmo salar in two rearing sites in the upper Connecticut River basin, New Hampshire. We contrasted effects of variation in foraging habitat availability and temperature on individual age-0 Atlantic sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
98
1

Year Published

2006
2006
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(108 citation statements)
references
References 32 publications
9
98
1
Order By: Relevance
“…Selection of habitat and biological response variables is one of the most important elements to a successful monitoring program. Examples of biological response variables at different levels include indices of fish community integrity (Karr and Chu, 2000), guilds or morphological groupings (Travnichek et al, 1995;Leonard and Orth, 1988;Chan, 2001), populations of fish or other aquatic species (Studley et al, 1995;Sabaton et al, 2008), threatened or endangered species, or individual and population level indices such as growth, reproductive success recruitment to a certain age class (Nislow et al, 2004). In all cases the selection should be driven by the project objectives established by the biological purpose of the flow management change and the hypothesized biological response.…”
Section: Designing a Monitoring Templatementioning
confidence: 99%
See 1 more Smart Citation
“…Selection of habitat and biological response variables is one of the most important elements to a successful monitoring program. Examples of biological response variables at different levels include indices of fish community integrity (Karr and Chu, 2000), guilds or morphological groupings (Travnichek et al, 1995;Leonard and Orth, 1988;Chan, 2001), populations of fish or other aquatic species (Studley et al, 1995;Sabaton et al, 2008), threatened or endangered species, or individual and population level indices such as growth, reproductive success recruitment to a certain age class (Nislow et al, 2004). In all cases the selection should be driven by the project objectives established by the biological purpose of the flow management change and the hypothesized biological response.…”
Section: Designing a Monitoring Templatementioning
confidence: 99%
“…The scale at which the habitat is measured should coincide with the habitat needs of the species or life stage and should be consistent with the conceptual framework and models used to develop hypotheses. Examples of different levels of physical habitat that have been used with some success in the evaluation of biological responses include mesohabitat (Parasiewicz, 2001), microhabitat (Gallagher and Gard, 1999), and selected eco-hydraulic measures (shear stress; spawning habitat for invertebrates and mussels; Statzner and Higler, 1986;Statzner et al, 1988;Gore et al, 1994;Chan, 2001) feeding and foraging stations (Nislow et al, 2004). These and other studies have shown that scale is critical for understanding flow-habitat linkages.…”
Section: Designing a Monitoring Templatementioning
confidence: 99%
“…Stalnaker 1979;Nehring and Anderson 1993;Jowett 1992Jowett , 1995Jowett & Biggs 2006). Empirical studies of fish population response to flow change mainly have been short term, which limits the inferences that can be made from them (Kraft 1972;Canton et al 1984;Harris et al 1991;Hayes 1995;Jowett 1995;Nislow et al 2004;Jowett et al 2005). Longterm studies are rare (Elliott et al 1997;Bell et al 2000;Gouraud et al 2001;Lobo´n-Cervia2 009), but are necessary to detect flow disturbance effects on recruitment and density dependence, and to understand carrying capacity limits (Bell et al 2000;Lobo´n-Cervia´2007, 2009Elliott 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Nislow et al (2004) found that age 0 salmon in a Connecticut River, New Hampshire, tributary grew more slowly in two low-flow years than in a highflow year where rearing space included expanded foraging locations. Growth rates were also negatively correlated with population density.…”
Section: Density Dependence and Interspecific Interactionsmentioning
confidence: 96%